Exploring a language-based solution to the problem of insecurity in Boko Haram dominated North Eastern Nigeria (2017)
For a couple of years, linguists in Nigeria have proposed language-based solution(s) for social integration and national development in Nigeria. However, to the best of our knowledge, none has suggested such for peace and security, especially in the turbulent and crises-ridden North-Eastern Nigeria, where Boko Haram insurgency has been the order of the day for some time now. This paper therefore explores the possibility of harnessing our linguistic resources through aggressive language planning to tackle this problem, with a view to attaining peace and security in Nigeria. The socio-linguistic theory of language planning which sees language as a national resource that can be used in improving social life, forms the theoretical framework for this paper. Data were collected from existing literature and interactions with students and lecturers from different geo-political zones in Nigeria. Knowing fully well that ethnicity-induced problem is invariably tied to the language question, a number of proposals are prescribed along this dimension. Some of them are an aggressive language planning, backed up by strong political will; the use of mother tongue as medium of education; the recognition of regional lingua francas and languages of Local Government Areas as official languages of government business; provision of compulsory pass in a second Nigerian language at WASCE; a deliberate policy of reward for scientific and technological research in local languages and the implementation of an obligatory language learning component as part of the mandate of the NYSC scheme. Rather than seeing our multilingual complexity as a curse from the tower of Babel, our languages should be seen as natural resources with which Nigeria is blessed for peace, security and national development.